1998
DOI: 10.1093/glycob/8.9.901
|View full text |Cite
|
Sign up to set email alerts
|

1-Thio- -D-galactofuranosides: synthesis and evaluation as  -D-galactofuranosidase inhibitors

Abstract: Beta-D-galactofuranosidase is a good chemotherapeutic target for the design of inhibitors, since beta-D-galactofuranose is a constituent of important parasite glycoconjugates but is not present in the host mammals. With this aim, we have synthesized for the first time alkyl, benzyl and aryl 1-thio-beta-D-galactofuranosides by condensation of penta-O-benzoyl-alpha,beta-D-galactofuranose with the corresponding thiols, in the presence of SnCl4as catalyst. The complete chemical and spectroscopical characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…4-Nitrophenyl β-D-galactofuranoside (10) was used as substrate, and lactone 9 was tested as a reference inhibitor (IC50 0.10 mM). 25 The enzymatic reaction was performed in the presence of thioglycosides 14b-16b, 18b and 19b at concentrations ranging from 0.15 to 1.25mM. We found that compounds 14b-16b, 18b are weak inhibitors (Figure 2), whereas 19b is a stronger inhibitor (IC50 135 µM).…”
Section: Issn 1424-6376mentioning
confidence: 85%
“…4-Nitrophenyl β-D-galactofuranoside (10) was used as substrate, and lactone 9 was tested as a reference inhibitor (IC50 0.10 mM). 25 The enzymatic reaction was performed in the presence of thioglycosides 14b-16b, 18b and 19b at concentrations ranging from 0.15 to 1.25mM. We found that compounds 14b-16b, 18b are weak inhibitors (Figure 2), whereas 19b is a stronger inhibitor (IC50 135 µM).…”
Section: Issn 1424-6376mentioning
confidence: 85%
“…Thus, a solution of 1a and thiourea in acetonitrile was heated under reflux in the presence of BF 3 ·OEt 2 to afford α-S-glycosyl isothiourea 2 (Scheme 1). In the NMR spectra of 2, the C-1 signal showed a strong upfield shift (relative to that of 1a) as observed for thioglycosylation of per-O-acylated furanoses [11,13] and the J 1,2 value (Ͻ1 Hz) indicated the α configuration for the anomeric center (1,2-trans thioglycoside). [19,20] As benzoylation of arabinose also provides β anomer 1b, the reaction of this compound with thiourea was conducted under the conditions employed for isomer 1a; Sglycosyl isothiourea 2 was obtained in good yield.…”
Section: Resultsmentioning
confidence: 67%
“…As 4-H is coupled with the adjacent methylene protons, the small coupling constant values (J 3ax,4 = 4.7 Hz, J 3eq,4 = 1.8 Hz) indicate that 4-H is equatorially oriented. Furthermore, the small value for the coupling between 1Ј-H and 2Ј-H (J 1Ј,2Ј Ͻ 1 Hz) is indicative of an 1Ј,2Ј-trans stereochemistry [11,13] (α anomeric configuration) for the furanose. Michael addition to sugar enone 3 was studied for other per-O-acylated furanoses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…215,216 The thiogalactofuranosides (Fig. 23) were easily obtained in good yields (generally higher than 85%) by S-glycosylation of penta-O-benzoyl-galactofuranose in the presence of 3 Following that example, we have recently synthesized a series of thioimidoyl furanosides as inhibitors of the a-L L-arabinofuranosidase AbfD3.…”
Section: Inhibitors Of Hydrolasesmentioning
confidence: 99%